Erratum (Current Neuropharmacology, 2022)
Due to an oversight, the title of an editorial was the same as the title of one of the manuscripts entitled as Current and Emerging Treatments for Methamphetamine Use Disorder, and now it has been replaced with the new one entitled “Insights Into the Complexity of Methamphetamine Actions in the Brain and Periphery in the Face of a 3rd Methamphetamine Abuse Epidemic, guest-edited by Dr. Anna Moszczynska, which was published in Current Neuropharmacology, 2021, Vol.19, No. 12.